Предмет: Алгебра, автор: ОпытныйФизик

(x^2−6x−9)^2=x(x^2−4x−9)
Решите еще одно пожалуйста, плохо врубаюсь в такие уравнения

Ответы

Автор ответа: mukus13
0
(x^2-6x-9)^2=x(x^2-4x-9)

Замена: 
x^2-4x-9=t

(t-2x)^2=x*t

t^2-4xt+4x^2-xt=0

t^2-5xt+4x^2=0

a=1

b=-5x

c=4x^2

D=(-5x)^2-4*1*4x^2=25x^2-16x^2=9x^2=(3x)^2

t_1= frac{5x+3x}{2} =4x

t_2= frac{5x-3x}{2} =x

x^2-4x-9=4x                 или     x^2-4x-9=x

x^2-8x-9=0                   или     x^2-5x-9=0

D=(-8)^2-4*1*(-9)=100 или D=(-5)^2-4*1*(-9)=25+36=61

x_1= frac{8+10}{2}=9                      или  x_1= frac{5+ sqrt{61} }{2}

x_2= frac{8-10}{2}=-1                    или   x_1= frac{5- sqrt{61} }{2}

Ответ:   frac{5б sqrt{61} }{2};  -1;  9

Похожие вопросы